2011
DOI: 10.1890/11-0461.1
|View full text |Cite
|
Sign up to set email alerts
|

Calcium constrains plant control over forest ecosystem nitrogen cycling

Abstract: Abstract. Forest ecosystem nitrogen (N) cycling is a critical controller of the ability of forests to prevent the movement of reactive N to receiving waters and the atmosphere and to sequester elevated levels of atmospheric carbon dioxide (CO 2 ). Here we show that calcium (Ca) constrains the ability of northern hardwood forest trees to control the availability and loss of nitrogen. We evaluated soil N-cycling response to Ca additions in the presence and absence of plants and observed that when plants were pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…However, it is unclear whether/how much within-watershed variation there is in the degree of chemical weathering or in the availability of cations to organisms. If present, landscape-scale variation in cation availability may have ecosystem consequences, since cation availability can influence decomposition and tree growth (Tripler et al, 2006;Kaspari et al, 2009), nitrogen cycling (Groffman and Fisk, 2011), microbial activity (Whittinghill and Hobbie, 2012) and root ingrowth (Cuevas and Medina, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is unclear whether/how much within-watershed variation there is in the degree of chemical weathering or in the availability of cations to organisms. If present, landscape-scale variation in cation availability may have ecosystem consequences, since cation availability can influence decomposition and tree growth (Tripler et al, 2006;Kaspari et al, 2009), nitrogen cycling (Groffman and Fisk, 2011), microbial activity (Whittinghill and Hobbie, 2012) and root ingrowth (Cuevas and Medina, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Ca can reduce the mobility and solubility of dissolved organic matter (OM) in some mineral soils by forming cation bridges that stabilize OM and reduce decomposition, leading to greater OM retention (Muneer and Oades 1989, Romkens et al 1996, Chan and Heenan 1999, Oste et al 2002, Mikutta et al 2007. Recent work has also demonstrated that increased Ca availability can lead to greater N uptake by plants and reduced microbial N cycling, thereby reducing potential ecosystem N losses via leaching (Groffman and Fisk 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…Leaf element concentrations strongly affect the productivity, functioning, and nutrient cycling of plant communities, and thus the response of an ecosystem to global change (Kerkhoff et al ., 2005; Amatangelo & Vitousek, 2008; Mueller et al ., 2010). For example, calcium (Ca) constrains the ability of northern hardwood forest trees to control the availability and loss of nitrogen (Groffman & Fisk, 2011). However, leaf element concentrations are largely uncertain variables in global carbon‐cycling models (Ren et al ., 2006).…”
Section: Introductionmentioning
confidence: 99%